Abundance, biomass, and structure of demersal ichthyofauna in the Pacific Ocean of Central America, based on fishery prospecting conducted on board the R/V Miguel Oliver - Benavides-Morera, Rosario (2020)
In order to expand knowledge about the structure and composition of demersal ichthyofauna on the Pacific of Central America, we analyzed samples collected from 98 sampling points on board the R/V Miguel Oliver from November 10 to December 16, 2010. Using a Lofoten net, trawl surveys were conducted for 30 minutes at each sampling point at different stratums and depths (1600 m maximum). The total sample (17507 specimens) was represented by cartilaginous fish and bony fish divided into 77 families and 158 species. Dicrolene filamentosa (12.27%) showed the highest abundance; Peprilus medius (35.67%) and Peprilus snyderi (12.49%) reported the most representative biomass along with Rhinoptera steindachneri (9.45%); in addition, Peristedion barbiger and Stomias atriventer were the most frequent species (both 2.71%). The coast between Costa Rica and Panama showed the highest diversity (H':3), while evenness showed uniform values along the studied area. In order to determine fish assemblages in response to depth, a spatial ordering was used showing a 3-set grouping (PERMANOVA, R = 0.54, P> 0.05). Furthermore, a canonical correspondence analysis shows enough evidence that the species distribution was influenced by salinity and temperature. Findings are ecologically significant indicating that ichthyofauna responds to particular environmental conditions and events. In addition, the paper highlights the importance of assemblages to assess how fish populations change as a result of the characteristics exhibited by water bodies